2007
DOI: 10.1677/joe-07-0028
|View full text |Cite
|
Sign up to set email alerts
|

High gastrin cell activity and low ghrelin cell activity in high-anxiety Wistar Kyoto rats

Abstract: Ghrelin is produced by gastric A-like cells and released in response to food deprivation. Interestingly, psychological stress also raises circulating ghrelin levels. This study compared plasma ghrelin levels in Sprague-Dawley (SPD) rats and high-anxiety Wistar Kyoto (WKY) rats. The two strains were also compared with respect to plasma gastrin, a gastric hormone with a pre-and postprandial release pattern opposite to that of ghrelin, and to the activity of the gastrindependent, histamine-forming ECL cells in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Thus, we proposed that ghrelin has anxiolytic-like effects and that ghrelin signaling is required for the anxiolytic-like effects of caloric restriction [9]. Our observations seem to be supported by a report showing that Wistar Kyoto rats, which are thought to display more anxiety-like behaviors than Sprague-Dawley and other rat strains, have lower plasma levels of ghrelin than Sprague-Dawley rats [24]. Furthermore, although stress-induced elevations in circulating ghrelin have been noted in both Wistar Kyoto and Sprague-Dawley rat strains, the magnitude of those elevations was significantly lower in the anxiety-prone Wistar Kyoto animals than in the Sprague-Dawley animals [11].…”
Section: Ghrelin's Role In Anxietysupporting
confidence: 75%
“…Thus, we proposed that ghrelin has anxiolytic-like effects and that ghrelin signaling is required for the anxiolytic-like effects of caloric restriction [9]. Our observations seem to be supported by a report showing that Wistar Kyoto rats, which are thought to display more anxiety-like behaviors than Sprague-Dawley and other rat strains, have lower plasma levels of ghrelin than Sprague-Dawley rats [24]. Furthermore, although stress-induced elevations in circulating ghrelin have been noted in both Wistar Kyoto and Sprague-Dawley rat strains, the magnitude of those elevations was significantly lower in the anxiety-prone Wistar Kyoto animals than in the Sprague-Dawley animals [11].…”
Section: Ghrelin's Role In Anxietysupporting
confidence: 75%
“…In contrast to these observations, increasing circulating ghrelin has been reported to produce anxiolytic-like responses, while no longer were these anxiolytic-like behavioral responses observed when GHSR-null mice were calorie restricted (Lutter et al, 2008). These findings are consistent with a report showing low ghrelin cell activity in high-anxiety Wistar Kyoto rats (Kristensson et al, 2007). The reasons for the conflicting results are currently unknown (Andrews, 2011).…”
Section: Ghrelin and Memory Depression And Anxietysupporting
confidence: 79%
“…Calorie-restricted wild-type mice showed anxiolytic-and antidepressant-like behavior in the elevated plus maze and forced swim test, respectively, as compared to wild-type mice (Lutter et al 2008). Also, high-anxiety WKY rats had lower circulating ghrelin than SPD rats in both the fasted and fed state (Kristensson et al 2007). Masayuki Kanehisa reported that in forced swimming tests, rats that received antisense DNA for ghrelin, immobilization time decreased.…”
Section: Discussionmentioning
confidence: 96%